2018
DOI: 10.1037/abn0000301
|View full text |Cite
|
Sign up to set email alerts
|

Negative cognitive style interacts with negative life events to predict first onset of a major depressive episode in adolescence via hopelessness.

Abstract: The hopelessness theory of depression is a prominent account of depression that posits that individuals with a negative inferential style are more likely to become hopeless when they experience negative life events (NLEs) and that hopelessness is a proximal cause of depression. There is strong evidence supporting the role of a negative inferential style in the pathogenesis of major depression; however, substantially less is known about the proposed role played by hopelessness. The cornerstone hypothesis of hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 63 publications
3
36
0
3
Order By: Relevance
“…Thus, it is possible that 2 years is an appropriate window within which to see the emergence of particular cognitive styles and their negative effects as stressful events unfold or accumulate for individuals. Indeed, Mac Giollabhui et al () found that negative cognitive styles combined with stressful events to predict the first onset of major depressive episodes among adolescents over this time interval. However, we do not know the ideal time lag at which to study these relationships, or if the time lag is even uniform across people, particularly in the absence of measures of intervening stressors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, it is possible that 2 years is an appropriate window within which to see the emergence of particular cognitive styles and their negative effects as stressful events unfold or accumulate for individuals. Indeed, Mac Giollabhui et al () found that negative cognitive styles combined with stressful events to predict the first onset of major depressive episodes among adolescents over this time interval. However, we do not know the ideal time lag at which to study these relationships, or if the time lag is even uniform across people, particularly in the absence of measures of intervening stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Mac Giollabhui et al (2018) found that negative cognitive styles combined with stressful events to predict the first onset of major depressive episodes among adolescents over this time interval. However, we do not know the ideal time lag at which to study these relationships, or if the time lag is even uniform across people, particularly in the absence of measures of intervening stressors.…”
Section: Limitationsmentioning
confidence: 95%
See 2 more Smart Citations
“…La depresión es un problema severo que afecta a más de 300 millones de personas en el mundo y es la principal causante de años de vida perdidos por discapacidad (APD = 7.5% en el año 2015), así como la principal afección que contribuye a las muertes por suicidio en el mundo (OMS, 2017). Los altos costes sociales y laborales asociados a esta problemática, y alta prevalencia en adolescentes y jóvenes en nuestro país y el mundo, así como su relación con las conductas suicidas hace necesaria una mayor comprensión del problema (Benjet, Borjes, Méndez, Albor, Cassanova, Orozco et al, 2016;Benjet, Borges, Medina-Mora, Martínez, Herrmosillo-De la Torre, et al, 2016;Borges, Benjet, Medina-Mora, Orozco, Familiar, Nock et al, 2010;Ferrari, Norman, Freedman, Baxter, Pirkis, Harris & Whiteford, 2014. La teoría de la depresión por desesperanza ha mostrado su validez y utilidad clínica en la predicción de la depresión con adolescentes y adultos jóvnes (Mac Giollabhui, Hamilton, Nielsen, Connolly, Stange, Varga, Burdette, Olino, Abramson, & Alloy, 2018).…”
Section: Introductionunclassified